Youth Australian footballers experience similar impact forces to the head as junior- and senior-league players: A prospective study of kinematic measurements - Hecimovich, M.; King, D.; Dempsey, A.; Gittins, M.; Murphy, M. (Journal of Sports Science & Medicine, 2018)
The aims of this study were to investigate the frequency, magnitude, and distribution of head impacts sustained by youth AF players over a season of games and report subjective descriptions on the mechanism-of-injury and sign and symptoms experienced. A prospective observational cohort study with participants (n = 19) (age range 13-14 yr., mean ± SD 13.9 ± 0.3 yr.) wearing a wireless impact measuring device behind their right ear over the mastoid process prior to game participation. Participants completed an individual post-game logbook providing feedback responses on recalling having a direct hit to their head with another player or the surface. Players experienced a mean (SD) of 5 (±4) impacts per-player per-game. The peak linear rotation (PLA) median, (95th percentiles) were 15.2g (45.8g). The median (95th percentile) peak rotational acceleration (PRA) were 183,117 deg/s2 (594,272 deg/s2). Median (95th percentile) Head Impact Telemetry Severity profile were 15.1 (46.1) and Risk Weighted Exposure Combined Probability were 0.0012 (0.7062). Twelve participants reported sustaining a head impact. Players reporting a head impact had a faster mean impact duration (t(25) = 2.4; p = 0.0025) and had a lower median PLA(g) (F(23,2) = 845.5; p = 0.0012) than those who did not report a head impact. These results show similar measurements to the older junior- (aged 17-19) and senior-league (20+) players. Furthermore, players who reported sustaining a direct or indirect impact during games had similar measurements to those who did not, thus highlighting the difficulty of concussion recognition, at least with youth. Future research may need to establish the relationship between concussion-like symptoms in the absence of an impact and in relation to concussion evaluation assessments such as the King-Devick and SCAT5.